Public Knowledge Regarding Adaptation and Mitigation Measures against Climate Change in Lima, Peru - Del Piero R. Arana-Ruedas; Yomira Cruz M.; Laura Soto-Guerra; Ewonny Ttito M. (Manglar)
Climate change is a current and globally significant issue. Many countries are working together with international agreements, developing strategies to mitigate the impacts it can generate. In Peru, public knowledge regarding climate change adaptation and mitigation measures has been a topic of great national interest but is also somewhat unknown or outdated. The aim of this study was to assess people's level of understanding regarding this subject. The methodology employed was quantitative, using surveys administered to citizens to analyze their perceptions of climate change measures. The results revealed that almost 80% of them have received information about climate change, but 95.9% think that climate change is real, so above 15% of the participants even without getting information about this global issue have a notion about it, 36.6% of the participants did not know about the Peruvian participation in the Paris Agreements as well as the Peruvian law of climate change where around 30% of surveyed are not aware of the regulation gave by Peruvian law, above of 60% of the participants did not know about Peruvian initiatives and actions linked to those measures. Lastly, above 60% of the participants think they are not involved in the adaptation and mitigation process. Also, above 90% of the participants have perceived a temperature rise. Finally, it is advisable to analyze the awareness programs implemented by the government to convey information about climate change adaptation and mitigation measures and keep studying regarding local-level climate change awareness.